The Reconstructive Metaverse – Collaboration in Real-Time Shared Mixed Reality Environments for Microsurgical Reconstruction - Necker, Fabian N.; Cholok, David J.; Shaheen, Mohammed S.; Fischer, Marc J.; Gifford, Kyle; El Chemaly, Trishia; Leuze, Christoph W.; Scholz, Michael; Daniel, Bruce L.; Momeni, Arash (Surgical Innovation, 2024)
Plastic surgeons routinely use 3D-models in their clinical practice, from 3D-photography and surface imaging to 3D-segmentations from radiological scans. However, these models continue to be viewed on flattened 2D screens that do not enable an intuitive understanding of 3D-relationships and cause challenges regarding collaboration with colleagues. The Metaverse has been proposed as a new age of applications building on modern Mixed Reality headset technology that allows remote collaboration on virtual 3D-models in a shared physical-virtual space in real-time. We demonstrate the first use of the Metaverse in the context of reconstructive surgery, focusing on preoperative planning discussions and trainee education. Using a HoloLens headset with the Microsoft Mesh application, we performed planning sessions for 4 DIEP-flaps in our reconstructive metaverse on virtual patient-models segmented from routine CT angiography. In these sessions, surgeons discuss perforator anatomy and perforator selection strategies whilst comprehensively assessing the respective models. We demonstrate the workflow for a one-on-one interaction between an attending surgeon and a trainee in a video featuring both viewpoints as seen through the headset. We believe the Metaverse will provide novel opportunities to use the 3D-models that are already created in everyday plastic surgery practice in a more collaborative, immersive, accessible, and educational manner.
CRIS-Team Scopus Importer:2024-06-28
Keywords: abdominal flaps; breast reconstruction; metaverse; microsurgery; mixed reality; preoperative planning; resident education